Validity and reliability of tooth color selection by smartphone photography and software applications - Abolghasem Mohammadi; Zeinab Bakhtiari; Fatemeh Mighani; Fatemeh Bakhtiari (Wolters Kluwer Medknow Publications, 2021)
Aim: This study assessed the validity and reliability of color selection by smartphone photography using two smartphone applications and Adobe Photoshop software. Settings and Design: In vitro comparative study. Materials and Methods: The validity and reliability of dental tooth shade recognition (DTSR), Chromatcher, and Adobe Photoshop were evaluated for color selection of shade tabs. The iPhone 7 camera in automatic mode was used for photography. Images were captured using Smile Lite with/without polarized filter and with camera flash. To assess the reliability, nine Vita Lumin Vacuum shade tabs were chosen and each was photographed for 10 times using Smile Lite. The reliability of DTSR, Chromatcher, and Photoshop in shade-taking was calculated. To assess their validity, 16 shade tabs of Vita Lumin Vacuum and 26 shade tabs of Vita 3D Master were photographed using the aforementioned lighting conditions. The color of photographs was calibrated and shade-taking was performed and compared with the shade suggested by SpectroShade as reference. Statistical Analysis Used: Data were analyzed using Two-way analysis of variance and Bonferroni post hoc test. Results: The reliability of Photoshop, DTSR, and Chromatcher was 98.88%, 63.3%, and 100%, respectively. The validity of Photoshop was significantly higher than other software programs (P < 0.05). Chromatcher had higher validity than DTSR (P < 0.05). Conclusion: Shade-taking by calibrated smartphone pictures and Adobe Photoshop has high validity and reliability.